A narrative review of acute care nurses' experiences nursing patients with intellectual disability: underprepared, communication barriers and ambiguity about the role of caregivers. Issue 11 (8th February 2017) - Lewis, Peter; Gaffney, Ryan J; Wilson, Nathan J
Abstract : Aims and objectives: To describe how nurses experience caring for people with intellectual disability in an acute care setting. Background: Recent advances in the care of people with intellectual disability in hospital are primarily based upon the experiences of people with intellectual disability and their caregivers. Little is known about the experiences of registered nurses caring for people with intellectual disability, yet the experiences of nurses in delivering care largely determine the quality of care experienced by people with intellectual disability and their caregivers. Methods: A narrative literature review using electronic database searches was conducted using variants of the terms disability, nursing and acute care. Results: Through our reading of the recent literature describing the experiences of nurses caring for people with intellectual disability in an acute care setting, we have identified three themes: (1) nurses feel underprepared when caring for patients with intellectual disability, (2) nurses experience challenges when communicating with people with intellectual disability and (3) nurses have ambiguous expectations of paid and unpaid caregivers. Conclusion: The enablers of and barriers to the delivery of nursing care in acute care settings need to be made explicit and researchers and nurses need to collaborate in the development, implementation and evaluation of care delivery strategies. Relevance to clinical practice: Nurses need to be adequately prepared to care for people with intellectual disability. Preparation should include dealing with the complexities of communicating with people with intellectual disability and practical experience of doing so in clinical and educational environments that ensure the safety and dignity of nurses and people with intellectual disability. Nurses need supportive strategies for developing therapeutic relationships with a range of informal and formal caregivers.